SOCIO-ECONOMIC CONSEQUENCES IN THE DOWN VALLEY OF THE SAN FRANCISCO RIVER (BRAZIL)AFTER THE CONSTRUCTION OF DAMS - Carlos Herminio De Aguiar Oliveira; Vera Lucia Alves Franca; Françoise Carpy Goulard; Maria Augusta Mundim Vargas (European Regional Science Association (ERSA), 2005)
This study aims at comparing the social and economic situation of the down valley of the San Francisco river in the State of Sergipe (Brazil), before and after the construction of the Sobradinho dam (1978), implemented to produce hydro-electric energy. Data of fourteen parameters have been collected in sixteen municipalities to compare the years 1970 with 2000. Statistical analysis and mapping of these data enhanced the comparative study. Due to the energy supply, the management of the river San Francisco boosted the development of important industrial complexes and consequently the implantation of big urban centers in the North – East of the country. But these infrastructures impacted negatively the environment at a local scale. It had unfavourable consequences for the populations living at the river sides downstream of the dam. For instance, the flow regulated at 2.060 m³/s prohibits natural floods of the adjacent alluvial plains as well as the feeding of the lagoons. As a consequence no traditional rice production and fishing could be practised anymore. Therefore national government, through the CODEVASF (public company for the development of the valley of the river Sao Fransisco), implemented an action plan to reduce these impacts downstream the Sobradinho dam. Important investments allowed the creation of irrigation belts and alevin production stations. Considering the initial desired level of living standard for the local population (job creation and increase of average annual income), and despite of the significant progress of the main indicators, it appears that these actions bring only partial and incomplete improvement. The water management, as a consequence of the dam, changed drastically the territory and its rural traditional activities. This study demonstrates the necessity to create a unit for territorial planning as well as a structure for integrated water management. Because water and its management play key roles on the identity, the construction and the development of a territory.
Keywords: 330